Renewable energy system design and evaluation: a case study / Vanessa Vincent... [et.al.] - Vincent, Vanessa; Boodlal, Donnie; Alexander, David; Parissram, Jaggernath; Maharaj, Rean (2023)
Due to the Paris Agreement and efforts of the United Nations Framework Convention on Climate Change towards stabilising global Greenhouse Gas Concentrations, countries are becoming receptive to the need for an energy transition. From a holistic sustainability viewpoint, this includes a renewable energy mix in power generation sectors. For early adopters like Trinidad and Tobago (T&T), it is important that analysis be conducted to investigate how renewable energy (RE) can be optimally integrated into the current energy mix. This paper considers the University of Trinidad and Tobago's Camden Campus, located in Couva as the study site. Though the study is specific to this site, the methodology, analysis, and conclusions are transferable to other similar sites. This study uses the Homer Pro Software to design, simulate, and optimize a hybrid PV-Wind energy system (using the least cost objective function). Given the electricity rates of the country, the "as is" case was the most cost-effective, excluding renewable energy penetration and greenhouse gas emissions reduction.